Global diversification discount and its discontents: A bit of self‐selection makes a world of difference - Chang, Sungyong; Kogut, Bruce; Yang, Jae‐Suk (Strategic Management Journal, 2016)
Research summary: The documented discount on globally diversified firms is often cited, but a correlation is not per se evidence that global diversification destroys firm value. Firms choose to globally diversify based on their firm attributes, some of which may be unobservable. Given these exogenous firm attributes, the decision to diversify globally is endogenous and self‐selected. Our study offers a replication of an earlier study. Using the same specifications save for the Heckman selection instrument, our results contradict past research that did not address endogeneity. We posit that the global premium should reflect the value of multinational operating flexibility. We use the 2008–2009 financial crisis as creating exogenous variation to permit a test for the positive change in firm valuation due to global diversification. During the 2008–2009 financial crisis, the premium associated with global diversification became larger and more significant than before the 2008–2009 financial crisis. The churn of subsidiaries entering and exiting countries increased during the crisis, pointing to the value of an operating flexibility to restructure the geography of the multinational network. In all, the results contradict past findings and provide evidence that operating flexibility is more valued during times of high volatility, thus generating the diversification premium. Managerial summary: There are thousands of multinational corporations that have been international for decades and some even longer. They undoubtedly learned that there is money to be made in international markets. Yet, the recent academic literature has found that foreign diversification destroys firm economic value. Our article uses a statistical technique that corrects for an obvious problem. Some firms invest overseas because they are facing troubles, for example, they are experiencing slowing growth and are exiting bad home markets. Once we correct for this “selection bias,” we find that global diversification, at worst, has no negative effect on value. However, during the financial crisis, the value of multinational companies increased. This finding is consistent with the option theory of multinational investment whereby operating in multiple countries permits firms to shift their activities among countries. Overall, our results indicate that there is a reason for why firms globalize: It is profitable . Copyright © 2016 John Wiley & Sons, Ltd.